2020
DOI: 10.3389/fonc.2020.00658
|View full text |Cite
|
Sign up to set email alerts
|

More Than a Metabolic Enzyme: MTHFD2 as a Novel Target for Anticancer Therapy?

Abstract: The bifunctional methylenetetrahydrofolate dehydrogenase/cyclohydrolase (MTHFD2) is a mitochondrial one-carbon folate metabolic enzyme whose role in cancer was not known until recently. MTHFD2 is highly expressed in embryos and a wide range of tumors but has low or absent expression in most adult differentiated tissues. Elevated MTHFD2 expression is associated with poor prognosis in both hematological and solid malignancy. Its depletion leads to suppression of multiple malignant phenotypes including proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 57 publications
3
65
0
Order By: Relevance
“…Aryal et al reported that glutamyl prolyl tRNA synthetase (EPRS) was selectively carbonylated in tumor breast tissue compared to normal breast tissue (31). MTHFD2, a metabolic enzyme involved in mitochondrial one-carbon folate metabolism and the high expression of MTHFD2 is associated with poor survival in breast cancer patients (32). As for NME3, Flentie et al suggested that the high expression level of NME3 increased overall survival of patients with breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Aryal et al reported that glutamyl prolyl tRNA synthetase (EPRS) was selectively carbonylated in tumor breast tissue compared to normal breast tissue (31). MTHFD2, a metabolic enzyme involved in mitochondrial one-carbon folate metabolism and the high expression of MTHFD2 is associated with poor survival in breast cancer patients (32). As for NME3, Flentie et al suggested that the high expression level of NME3 increased overall survival of patients with breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Mthfd2 is reported to play a role in embryonic development and pluripotent stem cells in mice [52,53]. In addition, Mthfd2 is associated with a poor prognosis in hematological and solid cancers [54]. Isg15 is involved in modulating the development of erythroid differentiation [55].…”
Section: Discussionmentioning
confidence: 99%
“…This makes MTHFD2 a potential target for CRC therapy. The first synthetic MTHFD1/2 inhibitor LY345899 has shown its anti-tumor activity in CRC [295]. Treatment of LY345899 led to reduced proliferative rate in primary CRC cells (SW480), its lymph node metastasis (SW620) and a liver metastatic derivative (SW620-LiM2), while no toxicity in the normal colon epithelial cells was observed [296].…”
Section: Targeting One-carbon Metabolismmentioning
confidence: 99%